LEGAL REGULATION OF METAVERSE AND THE PERSPECTIVES OF DIGITAL META FINANCIAL CENTER IN UZBEKISTAN - Turdialiev Mukhammad Ali Polatjon ogli (Scholar Express Journals, 2023)
This article analyzes some scientific and theoretical discussions about the legal regulation of the metaverse. In addition, it is also analyzed that a brief history of the metaverse, legal discussion of the law of the metaverse, definition and meaning of the meta-law, A look at the laws, regulation of the industry of the metaverse. In addition, the author attempts to analyze several legal issues in the metaverse such as copyright, intellectual property laws, contract law, tort law, false punishment law, NFT regulation, and taxes. As a result of these analyzes author offer to estlablishment of digital meta financial center in Uzbekistan
Keywords: metaverse; legal settlements; copyright; Uzbekistan